2012
DOI: 10.1093/brain/aws275
|View full text |Cite
|
Sign up to set email alerts
|

Myelin is dependent on the Charcot–Marie–Tooth Type 4H disease culprit protein FRABIN/FGD4 in Schwann cells

Abstract: Studying the function and malfunction of genes and proteins associated with inherited forms of peripheral neuropathies has provided multiple clues to our understanding of myelinated nerves in health and disease. Here, we have generated a mouse model for the peripheral neuropathy Charcot–Marie–Tooth disease type 4H by constitutively disrupting the mouse orthologue of the suspected culprit gene FGD4 that encodes the small RhoGTPase Cdc42-guanine nucleotide exchange factor Frabin. Lack of Frabin/Fgd4 causes dysmy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 81 publications
3
80
0
Order By: Relevance
“…This latter observation led to the hypothesis that myelin outfoldings represent a PIP 3 -dependent phenomenon, whereas tomacula are linked to the bulk of protein and lipid synthesis that is dependent on mTORC1 activation. This hypothesis is further supported by the fact that loss of either the MTMR2 phospholipid phosphatase (Bolino et al, 2000(Bolino et al, , 2004 or the guanosine nucleotide exchange factor for cdc42, FGD4 (Stendel et al, 2007;Horn et al, 2012), which binds to phospholipids, provokes demyelinating neuropathies with myelin outfoldings.…”
Section: The Pi3k/akt Pathway and Focal Hypermyelinationmentioning
confidence: 95%
“…This latter observation led to the hypothesis that myelin outfoldings represent a PIP 3 -dependent phenomenon, whereas tomacula are linked to the bulk of protein and lipid synthesis that is dependent on mTORC1 activation. This hypothesis is further supported by the fact that loss of either the MTMR2 phospholipid phosphatase (Bolino et al, 2000(Bolino et al, , 2004 or the guanosine nucleotide exchange factor for cdc42, FGD4 (Stendel et al, 2007;Horn et al, 2012), which binds to phospholipids, provokes demyelinating neuropathies with myelin outfoldings.…”
Section: The Pi3k/akt Pathway and Focal Hypermyelinationmentioning
confidence: 95%
“…CMT4H is an early-onset peripheral neuropathy caused by mutations in the Fdg4 gene that encodes FGD1-related actin filament-binding protein (Frabin), a guanine nucleotide exchange factor for the Rho GTPase Cdc42 [72]. Frabin is expressed in a wide variety of tissues, and its cellular function remains poorly understood.…”
Section: Endocytosis Impairmentmentioning
confidence: 99%
“…Frabin is expressed in a wide variety of tissues, and its cellular function remains poorly understood. A recent study has shown that shRNA-mediated depletion of endogenous Frabin leads to inhibition of transferrin receptor internalization in rat RT4 Schwann cells [72], suggesting a role of Frabin in regulation of endocytosis. Because CMT4H is a recessively inherited disease caused by loss-of-function mutations in Frabin, these results implicate endocytosis impairment as a potential pathogenic mechanism in CMT4H neuropathy.…”
Section: Endocytosis Impairmentmentioning
confidence: 99%
“…Myelin outfoldings similar to the pathology observed in Miz1⌬POZ mice are characteristic histopathological features in a limited number of inherited peripheral neuropathies (45)(46)(47)(48)(49)(50). The underlying pathomechanism has been attributed to dysregulated phosphoinositide levels and impaired vesicular transport (45, 46, 48, 50 -52).…”
Section: Deletion Of the Miz1 Poz Domain Affects Expression Of Genes mentioning
confidence: 94%